The Influence of Selection and Assignment Placement on the Quality of Human Resources in the Education Sector - Heni Rihani Manap (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2024)
Human Resources (HR) in an educational institution has an important role. The success of an educational institution is determined by several supporting factors, one of which is important is the role of human resources. Human resources in an educational institution are teachers and education staff. If the teachers and education staff are qualified, the institution can provide good educational services to its consumers, namely students and their parents. The quality of human resources can be in the form of the recruitment, selection, and job placement processes. Appropriate and appropriate placement will have an impact on work optimization and performance. In fact, employee creativity and initiative will develop and institutional activities can be carried out efficiently and effectively.